Embryo culture: Can we perform better than nature? - Vajta, G.; Rienzi, L.; Cobo, A.; Yovich, John (Elsevier Ltd, 2010)
Culture of preimplantation-stage embryos has always been a key element of laboratory embryology and has contributed substantially to the success of many assisted reproduction procedures. During the past decade, its importance has increased as extended in-vitro embryo culture and single blastocyst transfer have become indispensable parts of the approach to decreasing the chance of multiple pregnancy while preserving the overall efficiency of the treatment. However, in spite of the scientific and commercial challenge stimulating research worldwide to optimize embryo culture conditions, a consensus is missing even in the basic principles, including composition and exchange of media, the required physical and biological environment and even the temperature of incubation. This review attempts to summarize the controversies, demonstrate the fragility of some widely accepted dogmas and generate an open-minded debate towards rapid and efficient optimization. New approaches expanding the traditional frames of mammalian embryo culture are also discussed. Although some researchers suppose that the efficiency of the presently applied in-vitro culture systems have already approached the biological limits, authors are confident that substantial improvement may be achieved that may expand considerably the possibilities of future assisted reproduction in humans. © 2010, Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.